KONSEP ISTIHSAN ABU HANIFAH DALAM PANDANGAN AL-SYAFI’ - Azhar Azhar (JURNAL RAUDHAH, 2018)
Basic Formulation and root story of Istihsan appeared as law argumentation was beginning from Qiyas problem. Qiyas as one of the low argumentations incertain promblem could not applied. Because one of the essential principle element namely, illat was not able to fulfill the reguirement. On the other hand. Illat Qiyas that Will be oceurret as origin or the law similarity for that specific problem could not applied, because it was not compareble. Because of it, thatis must be finished by the other way which nearer canon laws purpose. Base or basic of consideration and istihsan formulation are like that, the it was appointed as one of the law argumentations. The formerly appeared by Abu Hanifah in his follower cirles.